TBL1XR1 promotes lymphangiogenesis and lymphatic metastasis in esophageal squamous cell carcinoma. Issue 1 (25th March 2014) - Liu, Liping; Lin, Chuyong; Liang, Weijiang; Wu, Shu; Liu, Aibin; Wu, Jueheng; Zhang, Xin; Ren, Pengli; Li, Mengfeng; Song, Libing
Abstract : Objective: Transducin (β)-like 1 X-linked receptor 1 (TBL1XR1) plays an important role in controlling the precisely regulated switch between gene repression and gene activation in transcriptional regulation. We investigated its biological function and clinical significance in esophageal squamous cell carcinoma (ESCC). Design: Immunoblotting and immunochemistry were used to determine TBL1XR1 expression in ESCC cell lines, ESCC clinical tissues and 230 clinicopathologically characterised ESCC specimens. The role of TBL1XR1 in lymphangiogenesis and lymphatic metastasis was examined by tube formation, cell invasion and wound-healing assays in vitro, and by a popliteal lymph node metastasis model in vivo. The molecular mechanism by which TBL1XR1 upregulates vascular endothelial growth factor C (VEGF-C) expression was explored using real-time PCR, ELISA, luciferase reporter assay and chromatin immunoprecipitation. Results: TBL1XR1 expression was significantly upregulated in ESCC, positively correlated with disease stage and patient survival, and identified as an independent prognostic factor for patient outcome. We found that TBL1XR1 overexpression promoted lymphangiogenesis and lymphatic metastasis in ESCC in vitro and in vivo, whereas TBL1XR1 silencing had the converse effect. We demonstrated that TBL1XR1 induced VEGF-C expression by binding to the VEGF-C promoter. We confirmed the correlation between TBL1XR1 and VEGF-C expression in a large cohort of clinical ESCC samples and through analysis of published datasets in gastric, colorectal and breast cancer. Conclusions: Our results demonstrated that TBL1XR1 induced lymphangiogenesis and lymphatic metastasis in ESCC via upregulation of VEGF-C, and may represent a novel prognostic biomarker and therapeutic target for patients with ESCC.